Observing Seasonal Variabilities of a Permafrost Landscape With PolSAR, InSAR and Pol-InSAR ... - Saporta, Paloma; Alonso-González, Alberto; Hammar, Jennika; Grünberg, Inge; Boike, Julia; Hajnsek, Irena (ETH Zurich, 2025)
Synthetic aperture radar (SAR) remote sensing is an established approach for observing Earth processes. The combination of different types of SAR acquisitions in polarimetric, interferometric, and polarimetric-interferometric frameworks is well studied for retrieving parameters of certain landscape features, such as forests and glaciers. These frameworks have only been rarely applied to permafrost regions, characterized by particular dielectric and structural properties, in particular frozen ground. Here, we investigate the effect of permafrost characteristics on the different SAR imaging modes. This study performs an analysis of the SAR data retrieved during an airborne campaign conducted by the German Aerospace Center (DLR) in the Canadian low Arctic. Established polarimetric SAR, SAR interferometry, and polarimetric SAR interferometry techniques are applied on the region of interest. For each of these techniques, results are analyzed in several dimensions. Winter and summer observables are compared, the ... : IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing, 18 ...